Phytochemical analysis of Schizophyllum commune Fr. and Microporus xanthopus (Fr.) Kuntze from Phulchowki, central Nepal - Dawadi, Prabin; Shyaula, Manita; Khadka, Christina; Raut, Jay Kant; Bhatt , Lok Ranjan (Scientific World, 2023)
Mushrooms are widely known for their therapeutic properties, which can be attributed to the secondary metabolites they produce. This study aims to evaluate different phytochemical constituents of two saprophytic mushrooms, namely Schizophyllum commune Fr and Microporus xanthopus (Fr.) Kuntze, collected from forest around Phulchowki, Lalitpur, Nepal. The total phenolic, flavonoid, vitamin C, β-carotene, and lycopene contents of S. commune were found higher than M. xanthopus (143.21 ± 0.003 vs. 108.45 ± 0.112 mg GAE/100 g; 91.55 ± 0.121 vs. 49.72 ± 0.073 mg QAE/100 g; 26.67 ± 0.015 vs. 3.15 ± 0.170 mg AA/100 g; 0.036 ± 0.001 vs. 0.013 ± 0.002, and 0.026 ± 0.002 vs. 0.01 ± 0.004 mg carotenoid/g; respectively) in the methanolic extracts. This study suggests that these mushrooms might have some medicinal values.